Giomer technology for preventive and restorative clinical management of erosive tooth wear: a case report - Silvério Agulhari, Maria Angélica; Giacomini, Marina; Rios, Daniela; Bombonatti, Juliana; Wang, Linda (Brazilian Dental Science, 2022)
Increasing prevalence of erosive tooth wear (ETW) is notable mainly due to current knowledge and its earlydiagnosis. Once teeth are functionally and/or esthetically affected, dental restorations may become necessary.Materials capable of interacting with the eroded dental tissue allied to their resistance to subsequent continuouserosive challenges are desirable. Giomer technology based on S-PRG (surface pre-reactive glass) filler has beenlaunching to provide benefits for the dental treatment due to its innovative multi-ionic release system, whichinvolves fluoride. This case report describes the employment of preventive and restorative materials basedon this technology for a patient under frequent erosive challenges and complaining about dental sensitivity.Patient reported immediate reduction on this sensitivity and the restorations has been followed up for 2 years,presenting satisfactory performance. S-PRG-based systems seem to be promissory for preventive and therapeuticmanagement of ETW used simultaneously with the patient compliance.KEYWORDSBiocompatible materials; Dental restoration; Smart polymer; Tooth erosion.